La Mecanique En Classe De Seconde Scientifique : Analyses Des Styles Pedagogiques Et Des Documents Iconographiques Dans Le Manuel Intitule Physique Chimie (Collection Arex), En Usage Actuel En Cote d’Ivoire - Nguessan, Kouamé (European Scientific Journal, ESJ, 2016)
This contribution sets out, through the analysis of the teaching styles, the texts and graphic material of the six chapters about Mechanics of the handbook Physique Chimie (Collection AREX, Les classiques africains) of the first years of high school science classes, to highlight the difficulties and obstacles that the teacher or the student face in using it.. The results of the analysis from the epistemological and didactic benchmarks knowledge to teach the mechanics show that the manual emphasizes the use of more informative teaching style and that of the illustrative figures to state the knowledge to be taught. Thus, the approaches used do not refer to a real problematization and do not allow students to be independent and productive; they are not actively and intellectually engage students in the learning process. Faced with the passivity of the student in the acquisition of knowledge, it thus seems necessary to include in the training of the teacher, a teacher training course based on understanding of texts and teaching styles to support a constructivist pedagogy class.